The complete chloroplast genome sequence of Corylopsis multiflora Hance var. nivea Chang - Ting Lv; Shuifei Chen; Rong Zhao; Ningjie Wang; Yanming Fang (Mitochondrial DNA. Part B. Resources, 2021)
Corylopsis multiflora Hance var. nivea Chang is a variety of the species C. multiflora in the family Hamamelidaceae and is classed as critically endangered (CR) in the Red List of China Higher Plants. The complete chloroplast genome sequence of this taxon (as C. multiflora var. nivea in GeneBank, accession number: MW043717) was reported in this study. The genome size is 158,993 bp in length, consisting of a pair of inverted repeat regions (IR, 26,213bp), large single copy (LSC, 87,895bp) and small single copy (SSC, 18,672bp). A total of 133 genes were annotated that included 87 protein coding genes (PCGs), 37 transfer RNA (tRNAs), and 8 ribosome RNA (rRNAs) and 1 pseudo gene. GC content were 38.01%. The Bayesian phylogeny tree showed that C. multiflora var. nivea formed a monophyletic branch with Corylopis coreana and Corylopsis spicata.